Takayasu Arteritis - Russo, Ricardo A. G.; Katsicas, María M. (Frontiers in Pediatrics, 2018)
Takayasu arteritis is an idiopathic granulomatous vasculitis of the aorta and its main branches. It is more prevalent among Asians and women, and it constitutes one of the more common vasculitides in children. Inflammation and intimal proliferation lead to wall thickening, stenotic or occlusive lesions, and thrombosis, while destruction of the elastica and muscularis layers originates aneurysms and dissection. Organ dysfunction -which is secondary to ischemia-, follows arterial structural changes. The aortic arch is the most frequently affected region, but thoraco-abdominal aorta, subclavian, common carotid, renal, mesenteric, iliac, and pulmonary arteries can also be involved. Carotid artery tenderness, claudication, ocular disturbances, central nervous system abnormalities, and weakening of pulses are the most frequent clinical features, which may be preceded by an inflammatory syndrome including fever, malaise, weight loss, and headaches. Particularly common in children is arterial hypertension. Laboratory abnormalities usually reflect inflammatory phases: high erythrocyte sedimentation rate and C reactive protein usually indicate disease activity. The diagnosis is confirmed by the observation of irregular vessel walls, stenosis, poststenotic dilatation, aneurysm formation, occlusion, and evidence of increased collateral circulation in angiography, MRA or CTA imaging, which are also good methods for monitoring disease activity. Pathogenesis remains unclear; genetic (such as HLA-associations) and microbial factors may play a role. Cell-mediated immune abnormalities (including proinflammatory cytokines) seem to drive the pathogenetic mechanisms; the role of described autoantibodies is still controversial. Early diagnosis and timely treatment are essential to achieve good outcomes. Medical treatment includes corticosteroids, immunomodulators such as methotrexate or cyclophosphamide, and biological agents for severe or refractory cases. TNF- and IL-6- inhibitors have been shown to be effective in uncontrolled series. Surgical artery repair/revascularization procedures are often needed for occlusive lesions and uncontrollable hypertension. The disease course is variable: remission is infrequent and most patients develop new arterial lesions over time. Mortality rates can be as high as 35%. Causes of death include congestive cardiac failure, myocardial infarction, and aneurismal rupture.